Transcriptome-associated metabolomics reveals the molecular mechanism of flavonoid biosynthesis in Desmodium styracifolium (Osbeck.) Merr under abiotic stress - Gao, Hongyang; Huang, Xi; Lin, Pengfei; Hu, Yuqing; Zheng, Ziqi; Yang, Quan (Frontiers in Plant Science, 2024)
The primary pharmacological components of Desmodium styracifolium (Osbeck.) Merr. are flavonoids, which have a broad range of pharmacological effects and are important in many applications. However, there have been few reports on the molecular mechanisms underlying flavonoid biosynthesis in the pharmacodynamic constituents of D. styracifolium. Flavonoid biosynthesis in D. styracifolium pharmacodynamic constituents has, however, been rarely studied. In this study, we investigated how salt stress, 6-BA (6-Benzylaminopurine) treatment, and PEG 6000-simulated drought stress affect flavonoid accumulation in D. styracifolium leaves. We integrated metabolomics and transcriptomic analysis to map the secondary metabolism regulatory network of D. styracifolium and identify key transcription factors involved in flavonoid biosynthesis.We then constructed overexpression vectors for the transcription factors and used them to transiently infiltrate Nicotiana benthamiana for functional validation. This experiment confirmed that the transcription factor DsMYB60 promotes the production of total flavonoids in Nicotiana tabacum L. leaves. This study lays the foundation for studying flavonoid biosynthesis in D. styracifolium at the molecular level. Furthermore, this study contributes novel insights into the molecular mechanisms involved in the biosynthesis of active ingredients in medicinal plants.